2017
DOI: 10.1016/j.jpubeco.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Evasive lying in strategic communication

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Second, the main aim of our analysis is to disentangle the e¤ects stemming purely from belief-driven communication costs, which motivates having such costs as the only source of informativeness of communication in our model. 17 See Khalmetski et al (2017) where this property of the receiver's investment is explicitly incorporated into the analysis in a similar setting.…”
Section: Solution Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the main aim of our analysis is to disentangle the e¤ects stemming purely from belief-driven communication costs, which motivates having such costs as the only source of informativeness of communication in our model. 17 See Khalmetski et al (2017) where this property of the receiver's investment is explicitly incorporated into the analysis in a similar setting.…”
Section: Solution Conceptmentioning
confidence: 99%
“…Examples include academic communication (Metsä-Ketelä 2012), doctor-patient interactions(Adolphs et al 2007), or corporate annual reports(Guo et al 2017). See alsoSerra-Garcia et al (2011) andKhalmetski et al (2017) for experimental evidence that senders indeed tend to use evasive and vague messages as a substitute for explicit lying.…”
mentioning
confidence: 99%
“…A second pair of experimental papers investigated how senders use vague or evasive language in simpler two-state strategic information transmission settings [25,26]. These found that deception through evasive messages such as feigning ignorance is less psychologically costly than deception through direct lies.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies providing support for the idea that people want to avoid blatant lies when they try to mislead others include Serra-Garcia et al (2011) and Khalmetski et al (2017). Serra-Garcia et al find that people rather deceive by means of a vague message that captures the truth.…”
Section: Introductionmentioning
confidence: 99%